Novel binder-free electrode materials for supercapacitors utilizing high surface area carbon nanofibers derived from immiscible polymer blends of PBI/6FDA-DAM:DABA. Issue 34 (12th April 2017) - Abeykoon, Nimali C.; Garcia, Velia; Jayawickramage, Rangana A.; Perera, Wijayantha; Cure, Jeremy; Chabal, Yves J.; Balkus, Kenneth J.; Ferraris, John P.
Abstract : High performing supercapacitor electrode materials were obtained by controlling the nanostructure of electrospun fibers derived from PBI/6FDD immiscible blends. Abstract : Carbon nanofibers with high surface area have become promising electrode materials for supercapacitors because of their importance in increasing energy density. In this study, a high free volume polymer, 6FDA-DAM:DABA (6FDD) was blended with polybenzimidazole (PBI) in different ratios to obtain different compositions of PBI/6FDD immiscible polymer blends. Freestanding nanofiber mats were obtained via electrospinning using blend precursors dissolved in N, N -dimethylacetamide (DMAc). Subsequently, carbonization, followed by CO2 activation at 1000 °C was applied to convert the fiber mats into porous carbon nanofibers (CNFs). The addition of 6FDD shows significant effects on the microstructure and enhancement of the surface area of the CNFs. The obtained CNFs show specific surface area as high as 3010 m 2 g −1 with pore sizes comparable to those of the electrolyte ions (PYR14 TFSI). This provides good electrolyte accessibility to the pore of the carbon materials resulting in enhanced energy density compared to the CNFs obtained from pure PBI. Electrodes derived from PBI:6FDD (70 : 30) exhibited outstanding supercapacitor performance in coin cells with a specific capacitance of 142 F g −1 at the scan rate of 10 mV s −1 and energy density of 67.5 W h kg −1 at 1 A g −1 (58 W h kg −1 at 10 A g −1 ) thus demonstrating promising electrochemical performance for high performance energy storage system.